PM2,5 and Hypertension - Desi Putri Utami; Al Asyary; Zakianis Zakianis (JUMP Health (Journal of Ultimate Public Health), 2020)
Hypertension is usually contributed by such factors including age, sex, heredity, education, smoking, obesity, physical activity and a history of other diseases such as kidney disease. In addition to these risk factors, hypertension can also be caused by particulate sources of air pollution. Air pollution has an impact on health including respiratory disorders, heart disease, cancer of various organs, reproductive disorders and hypertension. Some types of air pollutant most often found are Carbon Monoxide, Nitrogen Oxide, Sulfur Oxide, and dust particles such as Particulate Matter ≤ 2.5 μm (PM2.5).